Statistical position reconstruction for RPC-based thermal neutron detectors. (12th August 2021) - Morozov, A.; Margato, L.M.S.; Solovov, V.; Blanco, A.; Saraiva, J.; Wilpert, T.; Zeitelhack, K.; Roemer, K.; Höglund, C.; Robinson, L.; Hall-Wilton, R.
Abstract: Multilayer position-sensitive 10 B-RPC thermal neutron detectors offer an attractive combination of sub-millimeter spatial resolution and high (>50%) detection efficiency. Here we describe a new position reconstruction method based on a statistical approach. Using experimental data, we compare the performance of this method with that of the centroid reconstruction. Both methods result in a similar image linearity/uniformity and spatial resolution. However, the statistical method allows to improve the image quality at the detector periphery, offers more flexible event filtering and allows to develop automatic quality monitoring procedures for early detection of situations when a change in the detector operation conditions starts to affect reconstruction quality.